The role of teicoplanin in the treatment of SARS‐CoV‐2 infection: A retrospective study in critically ill COVID‐19 patients (Tei‐COVID study). Issue 7 (26th March 2021) - Ceccarelli, Giancarlo; Alessandri, Francesco; Oliva, Alessandra; Borrazzo, Cristian; Dell'Isola, Serena; Ialungo, Anna Maria; Rastrelli, Elena; Pelli, Massimiliano; Raponi, Giammarco; Turriziani, Ombretta; Ruberto, Franco; Rocco, Monica; et al.
Abstract: Teicoplanin has a potential antiviral activity expressed against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and was suggested as a complementary option to treat coronavirus disease 2019 (COVID‐19) patients. In this multicentric, retrospective, observational research the aim was to evaluate the impact of teicoplanin on the course of COVID‐19 in critically ill patients. Fifty‐five patients with severe COVID‐19, hospitalized in the intensive care units (ICUs) and treated with best available therapy were retrospectively analysed. Among them 34 patients were also treated with teicoplanin (Tei‐COVID group), while 21 without teicoplanin (control group). Crude in‐hospital Day‐30 mortality was lower in Tei‐COVID group (35.2%) than in control group (42.8%), however not reaching statistical significance ( p = .654). No statistically significant differences in length of stay in the ICU were observed between Tei‐COVID group and control group ( p = .248). On Day 14 from the ICU hospitalization, viral clearance was achieved in 64.7% patients of Tei‐COVID group and 57.1% of control group, without statistical difference. Serum C‐reactive protein level was significantly reduced in Tei‐COVID group compared to control group, but not other biochemical parameters. Finally, Gram‐positive were the causative pathogens for 25% of BSIs in Tei‐COVID group and for 70.6% in controls. No side effects related to teicoplanin use were observed. Despite several limitations require further research, in this study the use of teicoplanin is not associated with a significant improvement in outcomes analysed. The antiviral activity of teicoplanin against SARS‐CoV‐2, previously documented, is probably more effective at early clinical stages. Highlights: ‐Evidence from the scientific literature highlighted that a number of glycopeptide antibiotics have a potential antiviral activity expressed against Coronaviruses. Based on the aforementioned, teicoplanin was suggested as an alternative complementary option to treat also SARS‐CoV‐2 infected patients ‐Teicoplanin also remain a possible choice for treatment of Staphylococcus aureus superinfection, a major complication of respiratory viral infections and in COVID related pneumonia. ‐This is the first multicentric, retrospective, observational analysis of a real‐life cohort of critically ill patients with COVID‐19 complementary treated with teicoplanin, used with a double purpose: as empiric antibiotic treatment and as antiviral agent (Tei‐COVID group). A control group untreated with teicoplanin was also enrolled ‐The results of this study showed that teicoplanin does not impact on the crude mortality in critically ill COVID‐19 patients: the primary outcome of the study failed due to lack of statistical significance despite mortality being lower in the Tei‐COVID group than in the control group (35.2% vs. 42.8%) ‐On Day 14 from the ICU hospitalization, viral clearance was achieved in 64.7% patients of Tei‐COVID group and 57.1% of control group, without statistical difference. ‐Serum C‐reactive protein level was significantly reduced in Tei‐COVID group compared to control group. No statistically significant differences were observed for white blood cells and lymphocytes counts, kidney and liver function, PO2 /FiO2 and weaning from mechanical ventilation between the two groups at day 8. ‐ A possible explanation for these findings is that the antiviral activity of a drug is considered more effective at the onset of disease when viral replication and direct viral damage are still significant. As the disease progresses (the study enrolled critically ill patients), the damage is progressively sustained by pathogenic mechanisms not directly correlated with the presence of the virus, thus reducing the potential therapeutic role of antivirals at this stage.